Performance Analysis of Katiga Dam Irrigation Network Kuningan Regency - Rendy Romansyah; Bianca Nurul Azzahra; Akbar Winasis; Agung Prasetyo (Publikasi Indonesia, 2024)
Weir Third is one of the dams in Kuningan West Java. Dam Third, located on Jl. New East Ring Road, Tonjong Hamlet, Sangkanmulya Village, District Cigandamekar, Regency Kuningan. The distance from the city of Brass is not enough, more than 13 km towards the north and less than 24 km from Cirebon city to the south direction. Dam Third irrigates an area of ± 1,010 Ha, covering two districts: Regency Kuningan 348 Ha and Cirebon Regency 662 Ha. Buildings are mainly third in the form of channel parent and channel secondary. Research objectives This analyzes mark performance based on condition damage, knowing performance moment this, get weight component Channels and Buildings Weir Third. The author uses primary data and secondary data. Primary data is obtained from field observations​, while secondary data is from UPTD SUP Kalijaga – Cisanggarung. The methods used in the research Are qualitative nature, descriptive – and inductive. Research results show that the percentage performance component Channels and Structures on Dams Third based on conditions and functions, namely, Channel Primary and Secondary Weir Third with a percentage condition good 15%, condition medium 50%, condition damaged 34%, so the average condition channel Primary and Secondary Weir Third in Moderately Damaged Condition. The condition of the building on Dam Third is good at 7%, moderate condition at 85%, and damaged at 9%, so Weir Third's average condition is good. The result of the analysis calculation of rainfall rain and comparison of discharge needs with the debit of irrigation area availability shows that the debit availability river is bigger than the debit requirement, with thus water needs in irrigation areas being third in all-sufficient.